Anti-chance : a reply to Monod's chances and necessity - Schoffeniels, Ernest (Pergamon international library of science, technology, engineering, and social studies., 1976)
Anti-Chance: A Reply to Monod's Chance and Necessity is a critique of Jacques Monod's essay on the natural philosophy of modern biology. It explores the concepts of chance and necessity, central themes of Monod's work, and specifically whether life is the result of coincidence of diverse independent chains of causality or, on the contrary, whether it obeys the more fundamental concept of chance as proposed by the Danish School of physicists. Questions such as the chance or the inevitability of it all, the sites and sizes of the knowledge gaps and as to whether they will be filled with physics.